The Joint Application of Phosphorus and Ammonium Enhances Soybean Root Growth and P Uptake - Rosolem, Ciro Antonio [UNESP]; Batista, Thiago Barbosa [UNESP]; Dias, Patrícia Pereira [UNESP]; da Motta Neto, Laudelino Vieira [UNESP]; Calonego, Juliano Carlos [UNESP] (MDPI, 2022)
It has been shown that the joint application of phosphorus (P) and ammonium (N-NH+4) increases maize root proliferation and P acquisition by maize in alkaline soils, but this has not been shown in acidic soils for legumes. A greenhouse experiment was conducted to assess the effect of the joint application of P and NH4+ on soybean root growth and P acquisition. Soybean was grown in glass-walled pots without P, with monoammonium phosphate (MAP) and triple super phosphate (TSP) applied on the soil surface or localized. The soil P increased irrespective of the P source and localization. The rhizosphere pH was decreased by MAP, while the soil bulk pH was not affected. The TSP increased the root length by 55% and MAP by 76% over the control, and the number of root tips increased by 21% with TSP, 58% with MAP applied on the soil surface, and 78% with MAP localized. The soybean dry matter, N and P uptake, and P use efficiency were increased by P fertilization, mainly with MAP localized. The joint application of P and ammonium decreases the soybean rhizosphere pH, which results in root proliferation early in the cycle, and eventually in higher P uptake and use efficiency.
Keywords: Glycine max; phosphate fertilizer; phosphorus acquisition; root architecture